Analisis Estimasi Biaya Pengembangan Sistem Pada CV. Profile Image Studio Menggunakan Metode Use Case Point dan Extended Use Case Point - Maulida Sabrina; Yusi Tyroni Mursityo; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The occurrence of failure in development systems because of the bad cost estimation and scheduling. In estimating cost, CV. Profile Image Studio used a guesstimate method or guessing that is not based on evidence or theory, This makes CV. Profile Image Studio faces difficulties in justifying if there is a gap between estimated cost and actual cost. This research gives an insight into the comparative analysis of two estimation methods used for Sistem Informasi Manajemen Proyek (SIMPRO); Use Case Point and Extended Use Case Point. Furthermore, the scope will be allocated using Work Breakdown Structure approach that will makes the project scheduling is more structured, then be elaborated into a Gantt Chart. Use Case Point method produce the total cost required is Rp 169.233.405,00 with time allocation for 133,88 hours. Whereas Extended Use Case Point method produce total cost required is Rp 77.465.995.00 with time allocation for 61,28 hours. Based on the comparison of two methods, the calculation of cost estimation using Extended Use Case Point method is more recommended because it has smaller difference or gap with the actual cost that has value of Rp 44.150.000,00 than the calculation of cost estimation using Use Case Point method.